Cooperation between Regions of Spain with Countries of Middle East and North Africa in 1978—2022 - E. O. Muslimova (Научный диалог, 2023)
The question of the specifics of the international relations of the regions of Spain with the countries of the Middle East and North Africa is considered. Attention is paid to increasing the paradiplomatic activity of the regions in the context of globalization and the “new” regionalism. The results of a comparative analysis of the international political practices of the studied territories, a comprehensive study of the structure of political, socio-economic and other interaction of the regions of Spain with the territories of the countries of the Middle East and North Africa are presented. The question is raised about the institutional and constitutional design of the international activities of the regions. Particular attention is paid to the platforms of public diplomacy available to the autonomies of Spain. The author’s complex methodological approach is involved, theoretically based on the positions of regionalism and the theory of space. The lack of systematic knowledge about the connectivity of regions in the context of trans-regional integration runs counter to the needs and opportunities for studying the foreign policy of the territories of the European Union, Asia and the East. These circumstances determine the relevance of the research topic and dictate the need for a close study of the regions as territorial, functional and political units with varying degrees of influence in the context of foreign policy interaction. The theoretical scientific significance of solving this problem is substantiated by the formation of a new vision of interregional relations as a resource for mutual socio-economic and value enrichment.